Comparative analysis of bioenergy potential and suitability modeling in the USA and Turkey. (October 2022) - Guler, Dogus; Buttenfield, Barbara P.; Charisoulis, Georgios; Yomralioglu, Tahsin
Highlights: This research includes two study areas from different regions of the world, namely the USA and Turkey. Bioenergy potential and alternative locations for energy facilities are obtained. Fuzzification is used in the spatial representation of criteria. The bioenergy potential and facility suitability significantly depend on the study area. Open data and open source GIS tools are of great importance for reproducibility. Abstract: Both estimation and evaluation of electric energy potential from biomass are quite important in terms of renewable energy aims and policies. Identification of suitable locations for biomass energy facilities carries significant benefits from the rich potential for bioenergy. In this context, the paper applies a novel methodology in two study areas, namely Boulder, Colorado, United States (USA) and Selcuklu, Konya, Turkey. First, the study calculates energy potential from animal manure (i.e., cattle and sheep) and agricultural residues (i.e., corn, wheat, and barley). Second, location suitability is obtained by means of a Geographic Information Systems (GIS)-based approach that exploits fuzzy logic and the Best Worst Method (BWM). The result for bioenergy potential shows that Selcuklu (for 2019) and Boulder (for 2017) have 10, 834 kW and 1, 406 kW installed capacity. Differences in the pattern of suitable locations are also apparent. Selcuklu shows a broad spatial distribution of good but relatively lower suitability scores, while Boulder's scores are more localized and extremely high (approaching 0.99), due to differing patterns of steep terrain and to differing policies regulating green space. This information indicates that the electricity generation potential and facility location suitability for biomass energy clearly differ depending on differences in study area characteristics.